Hydraulic modeling for the assessment of flood hazard using the Iber software in the Amarante urban center - Martins, Márcia (2018)
Recently, there is an availability increase of hydraulic modeling software that allows the analysis and definition of several hydraulic variables, namely water depth and flow velocity, which are important parameters for the assessment and management of flood-prone areas. The growing use of this software is related with the fact of being Free and Open Source Software (FOSS), making possible the understanding of different approaches and providing most reliable and accurate results of flood-prone areas according different return periods. In this study it was used the freely hydraulic software Iber, a tool for two-dimensional modeling of water flow in rivers and estuaries that provides the hydraulic variables (water depth and velocity) required for the definition of flooded areas. The main objective of this work was the analysis of flood hazard at the city of Amarante (North of Portugal), a place frequently affected by these extreme events. Due to the huge concentration of activities and services along the flood-prone area, economic and social damages caused by floods in the historical and urban center of Amarante are very important. Therefore, hydraulic modeling of the flooded area was performed for different return periods (10, 100 and 500 years) using the Iber software. The main results shows the maximum extent of the flood, the water depth and the flow velocity for a specific return period and also, a flood hazard map for the return period of 100 years. This case study aims to contribute for a better management of flood risk, which is a challenge for competent authorities, namely the local civil protection, fireman's and municipality services.